Balancing Load Outgoing Transformator 2 di Politeknik Negeri Malang - Ika Noer Syamsiana; Budi Eko Prasetyo; Harry Hassidiqi; Salsha Faradilla Firdaus (Politeknik Negeri Malang, 2023)
In an electric power system, power quality is a major problem. One of the problems is load imbalance. According to IEEE (Institute of electrical and electronic engineer) number 446-1995 for load unbalance the limit value ranges from 5% to 20% on all phases. The monitoring panel system is useful for facilitating monitoring of power quality in real time so that the efficiency of electrical energy can be maintained. The object of this research is the load on Outgoing Transformer 2 at State Polytechnic of Malang. Measurements were carried out for 7 days. On Friday the average unbalanced load value is 6.75% with a neutral current of 34.4 A and conductor losses of 0.071 kW, while for 6 days it is classified as a balanced load with an average of 3.54-4.76% with neutral current of 10.5-24.6 A and conductor losses of 0.007-0.036 kW. So according to the IEEE standard std 446-1995 the Unbalance load value does not meet the standard on Friday, which exceeds the minimum standard of 5%. To get balanced loading results, it is necessary to carry out load balancing actions, namely by means of balancing. The recommendation for balancing is to move from phase R to phase S of 4.043 A and phase T of 2.695 A. After balancing, the % unbalanced load is obtained with an average of 3%, meaning that this load is classified as balanced with a neutral current of 13.44 A and losses conductor 0.014 kW.